IMPLEMENTASI KEBIJAKAN PERATURAN PEMERINTAH NOMOR 2 TAHUN 2011 PENYELENGGARAAN KAWASAN EKONOMI KHUSUS DI MARUNDA - Ade Sumardi (Faculty of Social and Political Science, 2017)
The development and advancement of science and technology policy to build special economic zone is apt to be realized. In order to realize a very important need common spatial planning, so that land use can be optimized according to the needs. In the process of development of special economic zones will have an impact of environment itself. This study is purposed to describe and analyze the factors that supporting and constraints in the implementation of Government Regulation No. 2 of 2011 about implementation of special economic zones in Marunda jakarta, while the methods used in this study indicate that the development of special economic zones have an impact on peoples in the region, which led to the loss of homes and livelihoods. This research, treatment of those affected by the development of special economic zones with the alternative involving the community as labor at the site of special economic zones adapted to the education and skills needed. Another alternative to the people who still pursue the profession as a fisherman accommodated by preparing FADs as a fishing location that does not interfere of the harbor traffic.